Wage structure differential and disability in Brazil: Underperformance or discrimination? - Nicole Rennó Castro; Gustavo Carvalho Moreira; Rodrigo Peixoto da Silva (EconomiA, 2019)
In 2013, 7.32% of the Brazilian population, or almost 15 million people, declared that they had some disability. Based on empirical evidence, this study sought to answer the following three questions: 1) Are men with disabilities paid less in the Brazilian labor market? 2) If so, is this predominantly due to differences in individual socioeconomic characteristics, underperformance, or is it a case of discrimination? 3) What are the main determinants of wage differential among disabled men? To answer these questions, we used data from a sample of men aged 18-65 working in Brazil's private sector to estimate Tobit wage equations and perform a twofold decomposition of the disabled-nondisabled wage differential by applying the traditional Oaxaca-Blinder technique. DeLeire (2001) methodology was then employed to isolate the roles of discrimination and underperformance in the analysis, which was performed separately by the severity of the disability effect on activities. It was found that male employees with disabilities that limit daily activities earn lower wages than comparably employed nondisabled men and that this difference increases with the severity of the disability; that the estimated wage differentials were associated with both discrimination and underperformance, especially the latter; that there was a wage "reward" for the disabled positively correlated with their level of education; that the onset period of a disability did not significantly affect wages; and that men with intellectual disabilities are the most wage disadvantaged. These results provide useful information for policy makers in Brazil when allocating resources to support people with disabilities.
Keywords: I19; J24; J31; 330; Labor market; Health; Person with disabilities statute